2001
DOI: 10.1046/j.1469-8137.2001.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal density and needle anatomy of Scots pine (Pinus sylvestris) are affected by elevated CO2

Abstract: • Morphological and anatomical characteristics of needles from different whorl levels were examined on Scots pines ( Pinus sylvestris ), grown for 4 yr under either ambient or elevated (ambient + 400 µ mol mol -1 ) CO 2 concentrations in open-top chambers.• Needle characteristics were studied using light microscopy, scanning electron microscopy and laser scanning confocal microscopy.• Under the elevated CO 2 treatment stomatal density was reduced on both adaxial and abaxial needle surfaces although the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 51 publications
(88 reference statements)
6
68
1
2
Order By: Relevance
“…In several studies it has been shown that elevated atmospheric CO 2 affects the morphology and structure of plant leaves by decreasing stomatal density (Woodward and Bazzaz 1988;Pearson et al 1995;Lin et al 2001) and increasing needle thickness and relative area of phloem (Lin et al 2001). Our results conclude that needle traces store some information about needle structure, and that this information can be obtained by using NTM.…”
Section: Discussionsupporting
confidence: 45%
“…In several studies it has been shown that elevated atmospheric CO 2 affects the morphology and structure of plant leaves by decreasing stomatal density (Woodward and Bazzaz 1988;Pearson et al 1995;Lin et al 2001) and increasing needle thickness and relative area of phloem (Lin et al 2001). Our results conclude that needle traces store some information about needle structure, and that this information can be obtained by using NTM.…”
Section: Discussionsupporting
confidence: 45%
“…The same phenomenon was found in a field study comparing Norway spruce trees with deficient and adequate B levels (Sutinen et al 2006). Increased numbers of sieve cells could be an adaptive response to increased need for transport of photoassimilate, as speculated by Lin et al (2001) for needles of Scots pine exposed to elevated CO 2 for four years.…”
Section: The Numbers Of Tanniferous Cells (T Cells) Were Calculated Amentioning
confidence: 99%
“…However, unlike the response to the drought and temperature, stomatal response to elevated CO 2 had contrasting results, varying from a decrease in SD (Lin et al, 2001;Woodward and Kelly, 1995) to a lack of stomatal acclimation within a single generation in wheat (Triticumaestivum L.) and sour oranges (Citrus aurantium L.) (Estiarte et al,1994). This may also be responsible for some exceptional cases observed in the northern and southern populations of the Dipcadi filamentosum studied.…”
Section: Discussionmentioning
confidence: 92%